Ex vivo vs. in vivo antibacterial activity of two antiseptics on oral biofilm - PRADA-LÓPEZ, ISABEL; QUINTAS, VICTOR; CASARES-DE-CAL, MARIA DE LOS ANGELES; SUAREZ-QUINTANILLA, JUAN ANTONIO; SUÁREZ-QUINTANILLA, DAVID; TOMÁS CARMONA, INMACULADA (Frontiers in Microbiology, 2015)
Aim: To compare the immediate antibacterial effect of two application methods (passive immersion and active mouthwash) of two antiseptic solutions on the in situ oral biofilm. Material and Methods: A randomized observer-masked crossover study was conducted. Fifteen healthy volunteers wore a specific intraoral device for 48 hours to form a biofilm in three glass disks. One of these disks was used as a baseline; another one was immersed in a solution of 0.2% Chlorhexidine (0.2% CHX), remaining the third in the device, placed in the oral cavity, during the 0.2% CHX mouthwash application. After a two-week washout period, the protocol was repeated using a solution of Essential Oils (EO). Samples were analysed for bacterial viability with the confocal laser scanning microscope after previous staining with LIVE/DEAD® BacLight™. Results: The EO showed a better antibacterial effect compared to the 0.2% CHX after the mouthwash application (% of bacterial viability= 1.16 ± 1.00% vs. 5.08 ± 5.79%, respectively), and was more effective in all layers (p<0.05). In the immersion, both antiseptics were significantly less effective (% of bacterial viability= 26.93 ± 13.11%, EO vs. 15.17 ± 6.14%, 0.2% CHX); in the case of EO immersion, there were no significant changes in the bacterial viability of the deepest layer in comparison with the baseline. Conclusions: The method of application conditioned the antibacterial activity of the 0.2% CHX and EO solutions on the in situ oral biofilm. The in vivo active mouthwash was more effective than the ex vivo passive immersion in both antiseptic solutions. There was more penetration of the antiseptic inside the biofilm with an active mouthwash, especially with the EO.